ANALISIS MUTU PENDIDIKAN DENGAN PENDEKATAN CONTROL CHART SHEWHART, FISHBONE DIAGRAM, FLOW CHART, DAN DIAGRAM SWOT - Irwan Maulana; Andi Sinjaya; R. Madhakomala (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This research aims to analyze the quality of education using various quality management tools, such as the Shewhart Control Chart, Fishbone Diagram, Flow Chart, and SWOT Analysis and their relationship to education. This approach provides a systematic framework for evaluating and improving the quality of education at various levels. The method used in this research is a literature study method by observing various kinds of documents from both books and journals.  The literature study in this research focuses on researching literature related to shewhar control charts, fishbone diagrams, flow charts, and SWOT diagrams and their relationship to education. Data collection is carried out by collecting library data, reading, recording and managing research results objectively, systematically, analytically and critically by looking at the year of publication and the most recent research. This was done to observe the importance of implementing Total Quality Management (TQM) in education, including the role of its approach to ensure the process is within the desired control. The results of this research show that an integrated Shewhart control chart, fishbone diagram, flow chart and SWOT diagram approach like this can improve the efficiency, effectiveness and quality of education